Fundamentals of Entreneurship ENT300 Klen Enterprise Business Model Canvas (BMC) / Nurul Izzah Zulkhpli - Zulkhpli, Nurul Izzah (2020)
KLEN Enterprise is an online retail company but I also have my showroom at Komplek Perniagaan Sultan Abdul Hamid, Alor Setar, Kedah. Besides that, people can also access me through email at klenenterprise@gmail.com or they can just direct call or whatsapp me at 04-7710832/019-7914589. My company sells skincare product. To be specific, it is a beauty toner. My toner is not an ordinary toner, it is a multifunction toner. It works from head to toe. It can be as a refreshing face mist, cleansing toner, essence, hair spray and many more! So my customers does not need to buy it in separate product where they can just get all those functions in my toner.